Conformational dynamics of the Hsp70 chaperone throughout key steps of its ATPase cycle - Rohland, Lukas; Kityk, Roman; Smalinskaitė, Luka; Mayer, Matthias P. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
The ATP-dependent Hsp70 chaperones are central hubs of the cellular quality surveillance network, assisting the folding of proteins from their synthesis at the ribosomes to their degradation by the proteasome or lysosomes. How Hsp70s perform their many functions is currently unclear. Crystal structures of Hsp70 with bound ADP, ATP, or ATP and peptide revealed large differences in domain arrangements. To arrive at a molecular understanding of Hsp70s, we analyzed the dynamics of conformational changes on ATP binding to apo Hsp70, on client binding to Hsp70·ATP and on the effects of their J-domain protein cochaperone and nucleotide-exchange factor. Our data present important insights into the mechanics, allostery, and dynamics of Hsp70 chaperones.
Gesehen am 07.12.2023